2020
DOI: 10.1186/s13244-019-0824-5
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic MR contrast agents: evaluation of multiple-organ gadolinium retention in healthy rats

Abstract: Objectives: The purpose of this study was to compare Gd levels in rat tissues after cumulative exposure to four commercially available macrocyclic gadolinium-based contrast agents (GBCAs). Methods: Sixty-five male Sprague-Dawley rats were randomized to four exposure groups (n = 15 per group) and one control group (n = 5). Animals in each exposure group received 20 GBCA administrations (four per week of ProHance®, Dotarem®, Clariscan™, or Gadovist® for 5 consecutive weeks) at a dose of 0.6 mmol/kg bodyweight. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…In the absence of any data concerning the clinical significance of this retention, when a contrast-enhanced MRI examination is deemed necessary it would seem prudent to select the GBCA that is cleared rapidly from the brain and body leading to lower levels of retained gadolinium during the first months and years after administration. Of the three macrocyclic GBCAs available for clinical use, gadoteridol has been shown in numerous animal studies to clear most rapidly from brain and other body tissues [12][13][14][15]. Although reasons for the more rapid clearance remain unclear, it is possible the specific molecular features of the gadoteridol molecule (low molecular weight and viscosity, neutrality and high lipophilicity) are sufficient to promote more rapid elimination from the brain and other soft body tissues [14,15,34,35] and that this results in lower levels of retained gadolinium in the first weeks/ months after exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of any data concerning the clinical significance of this retention, when a contrast-enhanced MRI examination is deemed necessary it would seem prudent to select the GBCA that is cleared rapidly from the brain and body leading to lower levels of retained gadolinium during the first months and years after administration. Of the three macrocyclic GBCAs available for clinical use, gadoteridol has been shown in numerous animal studies to clear most rapidly from brain and other body tissues [12][13][14][15]. Although reasons for the more rapid clearance remain unclear, it is possible the specific molecular features of the gadoteridol molecule (low molecular weight and viscosity, neutrality and high lipophilicity) are sufficient to promote more rapid elimination from the brain and other soft body tissues [14,15,34,35] and that this results in lower levels of retained gadolinium in the first weeks/ months after exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Of the three macrocyclic GBCAs available for clinical use, gadoteridol has been shown in numerous animal studies to clear most rapidly from brain and other body tissues [12][13][14][15]. Although reasons for the more rapid clearance remain unclear, it is possible the specific molecular features of the gadoteridol molecule (low molecular weight and viscosity, neutrality and high lipophilicity) are sufficient to promote more rapid elimination from the brain and other soft body tissues [14,15,34,35] and that this results in lower levels of retained gadolinium in the first weeks/ months after exposure. Clearly, a lower amount of gadolinium retained in rat brain and body tissues in the first weeks/months after gadoteridol administration would equate to several years in humans, given that one rat year equates to roughly 30 human years [36] if findings in animals are considered indicative of the human situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the similar imaging performances of gadoteridol and gadobutrol and assuming similar commercial practicality, the choice of which GBCA to choose comes down to an evaluation of potential safety issues. Whereas prospective multicentre studies of gadobutrol and gadoteridol reveal no differences in terms of immediate contrast reactions [31][32][33][34], animal studies of gadolinium (Gd) retention suggest that gadoteridol is cleared much more from brain and other body tissues than gadobutrol [35][36][37][38][39] resulting in lower levels retained Gd for longer periods of time. However, no signs or symptoms associated with brain Gd retention have yet emerged despite concerted research effort [25][26][27][28], and while the possibility of long-term effects on human health is an area of concern [40], no data are yet available that point to differences between the macrocyclic GBCAs in terms of impact on long-term human health.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have largely confirmed differences between linear and macrocyclic GBCAs 4–10 and between simple and substituted linear GBCAs 11 in terms of the amount of Gd retained after single or daily cumulative exposures. Interestingly, however, animal studies have also revealed differences among the macrocyclic GBCAs in terms of the amount of Gd retained, particularly in the first days and weeks after exposure, with lower levels of Gd retained in rat brain and body tissues after cumulative exposure to gadoteridol than after cumulative exposure to identical doses of gadoterate meglumine and gadobutrol, suggesting more rapid clearance of gadoteridol in the first weeks after injection 11–14 . A previous study by Jost et al 14 looked at the long‐term elimination of Gd after cumulative GBCA exposure but did not begin determination of Gd levels in brain tissues until 5 weeks after the final GBCA administration.…”
mentioning
confidence: 99%